ANALISIS SEMIOTIKA KOSTUM THE REMIX NET. TV TEMA ETHNIC DAN FUTURISTIK - Rizky Iwan Maulana; Titin Suhartini; Veny Purba (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2015)
ABSTRACT The Remix is one of the Special Program who on aired by NET. TV. Electronic Music Dance (EDM) as the point of this show. The compettion for Indonesian dj or remixer who paired with the freatest singer in the country makes the show serve a hgreatest entertaiment and never shown in the other televison program. The show has a lot of division inside, one of the divison of this program who people talk about the most and outstanding are a Fashion Stylist team. They’re the one who responsible for the Costume and all the wardrobe for al the talent for this program and the look itself should be otstanding and have to combine the futuristic side to all the costumes. One episode of The Remix is very interesting is The 11th Episode on November 7th, 2015. This episode was themed